The message of Philippians Jesus our joy - Motyer, J. Alec (Leicester, UK IVP, 1984)
Includes bibliographical references.
"The Bible speaks today series has been placed in the library in memory of Gordon W. Craig, 1926-1990".
Keywords: Bible. N.T. Philippians -- commentaries